Applying an ecosocial framework to address racial disparities in suicide risk among black youth. Issue 12 (16th August 2021) - Cohen, Daniel R.; Lindsey, Michael A.; Lochman, John E.
Abstract: Suicide in Black youth is a major public health crisis. Given that racism is a core aspect of the lived experience of Black students in educational settings, efforts to reduce racial disparities in suicide risk must identify and address sources of racism in school contexts and facilitate culturally relevant coping strategies. This article highlights patterns associated with the emergence of risk in Black children and adolescents, applies the Ecosocial Theory of Disease Distribution to conceptualize a strategic approach to reducing racial disparities in suicide, and integrates empirical literature on the relations between racism and suicidality. Extant research findings are applied to conceptualize strategies specifically oriented towards reducing the incidence of suicidal behaviors in Black youth through treatment utilization and engagement strategies for school mental health services, the application of culturally relevant factors within school‐based prevention and treatment programs, culturally relevant risk assessment, and universal prevention using antiracist practices in schools.